RESPON PASAR ATAS PENGUNGKAPAN KEBERLANJUTAN PADA PERUSAHAN PERBANKAN DI INDONESIA: PERAN UKURAN PERUSAHAAN - Amrie Firmansyah; Navelya Hadi; Sheila Sheila; Estralita Trisnawati (Center for Economic Studies Universitas Katolik Parahyangan, 2021)
This study examines the effect of sustainability disclosure on firm value and examines the moderating role of firm size in the association between sustainability disclosure and firm value. This research data uses data and information on financial statements and stock prices of financial sector companies in the banking sub-sector listed on the Indonesia Stock Exchange. Data obtained from www.idx.co.id and www.finance.yahoo.com with an observation period of 2018-2020. Based on purposive sampling, this study obtained a total sample of 47 observations. Hypothesis testing is done by multiple linear regression. The results show that the disclosure of sustainability reports does not affect firm value. In addition, firm size does not have a role in strengthening the effect of sustainability disclosure on firm value. This research indicates that the Financial Services Authority needs to develop sustainability disclosures under globally applicable standards. In addition, the Indonesia Financial Services Authority needs to supervise the implementation of sustainability disclosures carried out by companies in the banking sub-sector in Indonesia.